“Control orgánico de Lorito verde (Empoasca fabae L.), en el cultivo del fréjol (Phaseolus vulgaris L.)” - Romero Troya, José Simón (2022)
This document deals with the organic control of the Green Parrot (Empoasca fabae L.), in the cultivation of beans (Phaseolus vulgaris L.). In recent years, the use of natural extracts has been an alternative in insect-plague combat. These extracts have gained importance due to the search for a balance between the environment, production and the human being, in which aspects such as the specific action on the objective, low or null impact on surrounding organisms and the environment, as well as its low or null impact on the crop. Among the conclusions, it was determined that the green parrot causes significant losses to farmers, since by attacking the plant it causes the yield to not be as expected. Carry out an integrated management of pests within the crop to reduce the damage caused in the different phenological stages by the Green Parrot. In addition, organic controls should be carried out as an alternative to reduce the use of pesticides. The concentrated extract of garlic and chili, in doses of 1.5 cc/L of water, allows controlling the main pests in bean cultivation, Neen is a natural insecticide-nematicide of botanical origin, especially as insect repellents (organic insecticides) and chili pepper and tobacco reduce the population before the attack of green lorito, showing greater efficiency.